Self-esteem and teacher performance educational institutions of Comas, 2014 - Ocaña Fernández, Yolvi (2017)
The present research seeks to explore the relationship between self-esteem and teaching performance in the educational institutions of Comas district. This is a non-experimental, cross-sectional descriptive and correlational study; the sample was made up of 363 teachers; the instruments used were Coopersmith Self-Es teem Questionnaire and the MINEDU Teaching Performance. The results showed there is a relationship between self-esteem and teaching performance in the educational institutions of Comas district.